Kepatuhan Penggunaan Alat Pelindung Diri (APD) pada Pekerja Kontruksi: Kajian Literatur tentang Pengaruh Faktor Individu dan Pendekatan Keselamatan Kerja - Almira Chiara Putri Nusantara; Andriyani Andriyani; Triana Srisantyorini (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Work accidents caused by non-compliance with the use of Personal Protective Equipment (PPE) still occur frequently in various industrial sectors. This study aims to identify factors that influence compliance with the use of PPE through a literature review. The research design used is a literature review with literature sources from 15 national journals published between 2020 and 2024, obtained from the Google Scholar database. The results of the analysis show that compliance in the use of PPE is influenced by workers' knowledge about Occupational Health and Safety (OHS), attitudes towards occupational safety, training and counseling received, supervision carried out by the company, and the availability and comfort of PPE. Individual factors such as age and education level also influence the level of compliance. This study concludes that improving compliance requires a comprehensive approach involving education, regular training, close supervision, and the provision of comfortable and adequate PPE. It is expected that companies can integrate a systematic work safety program to reduce the number of work accidents and create a safer work environment.